F@# pain! A mini-review of the hypoalgesic effects of swearing - Hay, Carlie M.; Sills, Jackson L.; Shoemake, Julia M.; Ballmann, Christopher G.; Stephens, Richard; Washmuth, Nicholas B. (Frontiers in Psychology, 2024)
Swearing, or the use of taboo language, has been repeatedly shown to induce hypoalgesia. While reliable hypoalgesic effects have been observed across studies, the mechanisms by which swearing influences pain and the optimal dosage of swearing remain poorly understood. Plausible mechanistic rationale for swearing’s impact on pain include sympathetic response, emotion, humor, distraction, aggression, state disinhibition, psychological flow, risky behavior, and self-confidence. It remains unknown how the intensity of the swear word, speech volume, frequency, or timing influences pain modulation. While the majority of evidence demonstrates the efficacy of swearing at attenuating acute pain responses, these studies have utilized healthy populations with controlled experiments in laboratory settings. Comparatively, less is known about how laboratory findings translate practically/clinically to diverse populations, various dosages, and different pain chronicities. A greater understanding of mechanistic underpinnings and practical implications are necessary to feasibly implement swearing as a therapeutic modality to combat pain. The purpose of the following mini-review is to provide an overview of the current evidence on swearing for the reduction of pain, speculate on plausible underlying mechanisms, and discuss the potential for optimization of swearing for real-world translation. Lastly, identifying knowledge gaps to aid in directing future research will be discussed.